Range extender mediates long-distance enhancer activity - Grace Bower; Ethan W. Hollingsworth; Sandra H. Jacinto; Joshua A. Alcantara; Benjamin Clock; Kaitlyn Cao; Mandy Liu; Adam Dziulko; Ana Alcaina-Caro; Qianlan Xu; Dorota Skowronska-Krawczyk; Javier Lopez-Rios; et al. (Nature, 2025)
Abstract Although most mammalian transcriptional enhancers regulate their cognate promoters over distances of tens of kilobases, some enhancers act over distances in the megabase range 1 . The sequence features that enable such long-distance enhancer–promoter interactions remain unclear. Here we used in vivo enhancer-replacement experiments at the mouse Shh locus to show that short- and medium-range limb enhancers cannot initiate gene expression at long-distance range. We identify a cis -acting element, range extender (REX), that confers long-distance regulatory activity and is located next to a long-range limb enhancer of Sall1 . The REX element has no endogenous enhancer activity. However, addition of the REX to other short- and mid-range limb enhancers substantially increases their genomic interaction range. In the most extreme example observed, addition of REX increased the range of an enhancer by an order of magnitude from its native 73 kb to 848 kb. The REX element contains highly conserved [C/T]AATTA homeodomain motifs that are critical for its activity. These motifs are enriched in long-range limb enhancers genome-wide, including the ZRS (zone of polarizing activity (ZPA) regulatory sequence), a benchmark long-range limb enhancer of Shh 2 . The ZRS enhancer with mutated [C/T]AATTA motifs maintains limb activity at short range, but loses its long-range activity, resulting in severe limb reduction in knock-in mice. In summary, we identify a sequence signature associated with long-range enhancer–promoter interactions and describe a prototypical REX element that is necessary and sufficient to confer long-distance activation by remote enhancers.